2019
DOI: 10.2217/imt-2018-0144
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota Predicts Lung Cancer Patients at Risk of Immune-Related Diarrhea

Abstract: Previous studies showed that some patients after the treatment of anti-programmed cell death protein-1 (anti-PD-1) antibodies experienced immune-related diarrhea. In this study, we aim to explore the association between intestinal microbiota and immune-related diarrhea. Methods: We obtained the fecal samples of 26 advanced lung cancer patients before the first dose of anti-PD-1 antibodies. Results: Eight of 26 patients experienced diarrhea after the treatment of anti-PD-1 antibodies. At the phylum level, our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Gut microbiota variation is correlated with the risk of immune-related diarrhea in lung cancer patients after the treatment of anti-programed cell death protein-1 (anti-PD-1) antibodies. Phascolarctobacterium, as well as Bacteroides and Parabacteroides were more abundant whereas Veillonella was lower in patients without diarrhea (Liu T. et al, 2019). Given the vital role of gut microbiota in shaping immune responses, the influence of antibiotics on the efficacy of immunotherapy in patients with lung cancer was studied by a retrospective analysis.…”
Section: Lung Cancermentioning
confidence: 99%
“…Gut microbiota variation is correlated with the risk of immune-related diarrhea in lung cancer patients after the treatment of anti-programed cell death protein-1 (anti-PD-1) antibodies. Phascolarctobacterium, as well as Bacteroides and Parabacteroides were more abundant whereas Veillonella was lower in patients without diarrhea (Liu T. et al, 2019). Given the vital role of gut microbiota in shaping immune responses, the influence of antibiotics on the efficacy of immunotherapy in patients with lung cancer was studied by a retrospective analysis.…”
Section: Lung Cancermentioning
confidence: 99%
“…(2018) observed that Alistipe s is one of the colon rectum cancer‐enriched genera. Diarrhea is the most common adverse immune‐related, and the increase in Phascolarctobacterium may aggravate this risk (Liu et al., 2019). The report also pointed a massive decrease in the genus of Phascolarctobacterium related to colonic inflammation (Bajer et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Data shows that gut microbiota has a strong influence on the efficacy of cancer immunotherapy, chemotherapy, and radiotherapy [ 77 ]. Monoclonal antibodies, such as anti-PD-1/PD-L1 or anti-CTLA-4, are successfully used in cancer immunotherapy [ 24 , 31 , 78 , 79 ]. There are many reports stating that microbiome has a significant role in enhancing or reducing the efficacy of immunotherapy [ 80 ] and disturbance of the physiological gut microbiome may lead to primary resistance to immune checkpoint therapy [ 32 , 80 , 81 ].…”
Section: The Impact Of Microbiome On the Efficacy Of The Immunotherapymentioning
confidence: 99%
“…Data shows that Bacteroides , Parabacteroides , and Firmicutes were more abundant in the gut of patients without diarrhea. Veillonella was less abundant in this kind of patients [ 79 ].…”
Section: The Impact Of Microbiome On the Efficacy Of The Immunotherapymentioning
confidence: 99%